2004
DOI: 10.1038/sj.npp.1300401
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Nicotine Exposure Alters the Response to Nicotine Administration in Adolescence: Effects on Cholinergic Systems During Exposure and Withdrawal

Abstract: Maternal smoking during pregnancy increases the likelihood that the offspring will become smokers in adolescence. In the current study, we evaluated effects of prenatal and adolescent nicotine exposure in rats to assess whether there is a biological basis for this relationship. Pregnant rats were given nicotine or vehicle throughout pregnancy and the offspring then again received nicotine or vehicle during adolescence (postnatal days PN30-47.5), using a regimen (6 mg/kg/day by subcutaneous infusion) that produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 67 publications
5
67
0
1
Order By: Relevance
“…In addition, nicotine withdrawal has been found to induce cholinergic hypoactivity in adolescent rodents with prenatal exposure to nicotine (Abreu-Villaca et al, 2004b). Given that reductions in cholinergic neurotransmission disrupt memory in humans (Rosier et al, 1998(Rosier et al, , 1999Mewaldt and Ghoneim, 1979), the present observations of significant decrements in visuospatial memory that emerge during nicotine withdrawal in adolescent smokers with exposure to active maternal smoking are consistent with these preclinical findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, nicotine withdrawal has been found to induce cholinergic hypoactivity in adolescent rodents with prenatal exposure to nicotine (Abreu-Villaca et al, 2004b). Given that reductions in cholinergic neurotransmission disrupt memory in humans (Rosier et al, 1998(Rosier et al, , 1999Mewaldt and Ghoneim, 1979), the present observations of significant decrements in visuospatial memory that emerge during nicotine withdrawal in adolescent smokers with exposure to active maternal smoking are consistent with these preclinical findings.…”
Section: Discussionsupporting
confidence: 85%
“…Animal studies have also demonstrated evidence that prenatal exposure to nicotine impairs cholinergic responsiveness in adolescence, blunting the ability of nicotine to upregulate nAChRs and desensitizing neuronal responses to nicotine challenge (Abreu-Villaca et al, 2004b;Seidler et al, 1992). In addition, nicotine withdrawal has been found to induce cholinergic hypoactivity in adolescent rodents with prenatal exposure to nicotine (Abreu-Villaca et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that way, neurotoxicant effects of nicotine may then explain, in part, the existence of a vulnerable subpopulation of adolescents who are especially predisposed to nicotine addiction (Cornelius et al, 2000;Kandel et al, 1994;Niaura et al, 2001). The fact that prenatal nicotine exposure by itself elicits widespread, lasting alterations almost certainly contributes to long-term changes involving multiple neurotransmitter systems and circuits throughout the brain (Abreu-Villaça et al, 2003a-c; Levin and Slotkin, 1998;Roy et al, , 2002Sabherwal, 1994, 1998;Slotkin, 1992Slotkin, , 1998Slotkin, , 1999Slotkin, , 2002Slotkin et al, 2002;Trauth et al, 2000aTrauth et al, -c, 2001Xu et al, 2001Xu et al, , 2002Xu et al, , 2003 and thus future studies need to address how these pathways are affected by sequential prenatal and adolescent nicotine exposure; a parallel study from our group has already found similar worsening of outcomes directed toward cholinergic systems (Abreu-Villaça et al, 2004) but, given the more generalized neurotoxicant effects, there is no reason to suspect that the synaptic effects will be limited to acetylcholine. Our findings in rats thus point to specific biological bases for the increased susceptibility of adolescent smokers to nicotine dependence, and particularly the subpopulation of adolescents whose mothers smoked during pregnancy; we suggest that this higher vulnerability comprises components of nicotine neurotoxicity as well as selective alterations in synaptic communication.…”
Section: Discussionmentioning
confidence: 72%
“…More specifically, the maturation of central cholinergic systems involved in learning, memory, and psychostimulant responses is consolidated during the periadolescent period Nadler et al, 1974;Zahalka et al, 1993), and an important aspect of this period is that neuronal stimulation induces synaptic rearrangement (Scheetz and Constantine-Paton, 1994), which indicates that adolescent brain is vulnerable to central nervous system stimulants. As an acetylcholine analog, the nicotinic acetylcholine receptors are the primary cellular mediators of nicotine's effects (Abreu-Villaça et al, 2003, 2004b. As for ethanol, it directly influences the function of various ligandgated ion channels, including nicotinic receptors (for review : Grant, 1994).…”
Section: Neurobiology Of Nicotine Vs Ethanol Interactionsmentioning
confidence: 99%